Electromagnetic Operation Environment Analysis of Middle-low-speed Maglev Train - QI Hong-feng (机车电传动)
With electromagnetic finite element method, leakage magnetic field distribution of electromagnets and linear traction motor was simulated and calculated, the results of which were compared to test reports of electromagnetic radiation field of CMS04 middle-lowspeed maglev train carried out by Institute of Electrical Engineering Chinese Academy of Science, which proved that middle-low-speed maglev train transport system was a kind of green urban rail transit system with good electromagnetic environment.